Activity induced first order transition for the current in a disordered medium - Demaerel, T.; Maes, C. (Condensed Matter Physics, 2017)
It is well known that particles can get trapped by randomly placed obstacles when they are pushed too much. We present a model where the current in a disordered medium dies at a large external field, but is reborn when the activity is increased. By activity we mean the time-variation of the external driving at a constant time-averaged field. A different interpretation of the resurgence of the current is that the particles are capable of taking an infinite sequence of potential barriers via a mechanism similar to stochastic resonance. We add a discussion regarding the role of “shaking” in processes of relaxation. Вiдомо, що частинки можуть попасти в пастку завдяки випадково розташованим перешкодам, якщо вони зазнають сильних зiткнень. Ми представляємо модель, де струм у невпорядкованому середовищi зникає при великому зовнiшньому полi, але вiдновлюється при зростаннi активностi. Пiд активнiстю ми маємо на увазi часову варiацiю зовнiшнього усередненого за часом постiйного поля. Iнше пояснення вiдновлення струму полягає в тому, що частинки здатнi проходити нескiнченну послiдовнiсть потенцiальних бар’єрiв через механiзм, подiбний до стохастичного резонансу. Ми також обговорюємо роль “струшування” в процесах релаксацiї.